(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The paper is a result of my interdisciplinary way to deal with Gender Studies and Stories of Alice Munro, Canada’s praised innovative writer the Nobel Laureate. It is a clever thought of interdisciplinary investigation of Gender Studies as origination and how Gender Studies are fictionalized in the tales of Munro. FictionStorytelling is the best medium to address the issues, for example, sexual orientation separation and sex exploitation identified with Gender Studies. This paper tries to investigate the socialization of young female children – the gendering or sex teaching, the philosophy of sexual orientation arrangement of the organization of male-centric society. It presents the function of these two trains in changing the gendered society.